(untitled) (Revista Internacional de Folkcomunicação, 2020)
The practices, narratives and cultural aspects of Companhia Teatral Arte Viva (Santa Cruz, Rio Grande do Norte, Brazil) are analyzed in the communicational and media scope. The report highlights its representative characteristics and the social interaction between the company and the public, as well as evidencing the observation of an original phenomenon: the expression and resistance of the theaters in association with their folkmidiática contextualization when addressing the theatricality that occupies the public space and it demonstrates, in its essence, the vocation. Folk-comunication; Street Theater; Arte Viva theater company.